A Study of Response Inhibition in Overweight/Obesity People Based on Event-Related Potential - Liu, Ze-Nan; Jiang, Jing-Yi; Cai, Tai-Sheng; Zhang, Dai-Lin (Frontiers in Psychology, 2022)
Objective: To investigate the characteristics of response inhibition of overweight/obese people, using behavior experiments combine with neural electrophysiological technology and discussing the difference in impulse level between obesity/overweight and normal weight people through EEG data, questionnaire, and behavior experiment. Method: (1) All participants completed the Go / Nogo task, meanwhile, behavior data and 64 channel EEG data were recorded. (2) Participants completed the Stop Signal task and behavior date was recorded. Results: (1) During Go / Nogo task, no significant differences were found in reaction time, omission errors of the Go task between the two groups, while commission errors of the Nogo task of the control group were significantly greater than the overweight/obesity group. (2) About SSRT during the Stop Signal Task, the interaction of stimulus type(high calorie food picture、 low-calorie food picture） and group(control group, overweight/obesity group） was significant(p=0.008). (3) No significant differences were found between the two groups in amplitude and latency of N2. About the amplitude of P3, the interaction of task type(Go task, Nogo task）, electrode point(Cz, CPz, Pz)and groups were significant (p=0.041), the control group P3 amplitude were significantly greater than overweight/obesity group during the Nogo task. Regarding about latency of P3, the interaction of group and electrode point were not significant(p=0.582)，but the main effect of task type was significant(p=0.002). Conclusions: (1) In terms of behavioral outcomes, overweight-obese subjects had lower dominant response inhibition and response cessation compared to normal weight subjects. (2) In terms of EEG results, overweight-obese subjects showed no difference in processing speed and level of conflict monitoring for early inhibitory processing compared to normal weight subjects, but there was a deficit in behavioral control for late inhibitory processing.